Pharmacy-related research for health in the Arab region: An analysis informed by WHO's global strategy on research for health - Dalia Bajis; Magda Daifi; Mohamed Ezzat Khamis Amin (Elsevier, 2022)
In 2012, WHO (the World Health Organisation) published a strategy on research for health based on the premise that policies and practices in support of health worldwide should be grounded in the best scientific knowledge derived from high-quality research. This strategy focuses attention on five interrelated goals: organisation, capacity, priorities, standards, and translation.1 Whilst knowledge production and publication in many Arab countries have been on the rise, the overall global share of the Arab region in health research publication is smaller than its global share of population or wealth.2 Inspired by the five WHO goals on research for health, this commentary shares factors and recommendations for consideration to enhance pharmacy-related research in the Arab region. These recommendations include establishing strategies for pharmacy-related research to address the context and local needs of the host country, creating intranational and intraregional collaborative research avenues, investing in research capacity, and fostering a culture of research in the workplace.